2021
DOI: 10.2196/19737
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Proactively Offered Online and Telephone Support Services Targeting Multiple Health Risk Behaviors Among Vocational Education Students: Process Evaluation of a Cluster Randomized Controlled Trial

Abstract: Background A high proportion of vocational education students smoke tobacco, have inadequate nutrition (ie, low fruit and vegetable intake), drink alcohol at risky levels, or are physically inactive. The extent to which vocational education students will sign up for proactively offered online and telephone support services for multiple health risk behaviors is unknown. Objective The aim of this study is to examine the uptake of proactively offered onlin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…This study found that vocational education students' uptake of proactively offered online support services ranged from 5.5-14.3% across SNAP risk behaviours while uptake of proactively offered telephone services was between 0.9-7.0% across these risk behaviours [29]. Uptake of support services targeting nutrition and physical activity (12.7-14.5%) appeared higher than that of services for smoking and alcohol (5.5-6.8%) [29]. In relation to modifying multiple SNAP risk behaviours, only 5.8% of vocational education students signed up for online or telephone support to modify two or more health risk behaviours [29].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…This study found that vocational education students' uptake of proactively offered online support services ranged from 5.5-14.3% across SNAP risk behaviours while uptake of proactively offered telephone services was between 0.9-7.0% across these risk behaviours [29]. Uptake of support services targeting nutrition and physical activity (12.7-14.5%) appeared higher than that of services for smoking and alcohol (5.5-6.8%) [29]. In relation to modifying multiple SNAP risk behaviours, only 5.8% of vocational education students signed up for online or telephone support to modify two or more health risk behaviours [29].…”
Section: Introductionmentioning
confidence: 79%
“…For ADIS, participants provided their contact details and were e-mailed or sent a text with the ADIS phone number to contact. This study found that vocational education students' uptake of proactively offered online support services ranged from 5.5-14.3% across SNAP risk behaviours while uptake of proactively offered telephone services was between 0.9-7.0% across these risk behaviours [29]. Uptake of support services targeting nutrition and physical activity (12.7-14.5%) appeared higher than that of services for smoking and alcohol (5.5-6.8%) [29].…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations